Methodological Approaches in Grammatical Analysis in the Works of Rukn al-Dīn al-Jurjānīy (d. 730 AH): Tanbīhāt as a Model (Journal of the College of Basic Education, 2025)
Arabic grammar serves as a tool for the correction of speech, the identification of word relationships, the development of innate linguistic competence, and as a monitor over what the speaker articulates or the writer records. Scholars exerted great effort in constructing and formulating it until it reached us as a stable, well-established science—distinguished by precision in textual analysis and the derivation of grammatical rulings, following a balanced path between structures and meanings. Grammatical authorship subsequently became active and took on diverse directions, aiming to teach this discipline to students and young learners. Scholars relied on a range of methods, especially in their commentaries, with the goal of achieving comprehension and clarity. This grammatical scholarship came to be characterized by methodological approaches, among which was the use of grammatical tanbīhāt, widely present in their works as a means to draw the learner’s attention. These tanbīhāt sometimes appeared as corrections or illuminative remarks during the explanation of grammatical issues. This practice began early in the tradition, gained momentum, and flourished with later grammarians such as al-Jurjānīy.